My Etruscan face / Gianna Patriarca. - Patriarca, Gianna. (Quattro Books, 2007)
"My Etruscan Face is Gianna Patriarca's 6th book of poetry since the release in 1994 of the award-winning Italian Women and Other Tragedies. The poet continues her struggle with the masks of identity, the inheritance of the lost landscape of Italy, and the bittersweet balm of aging." -- P. 4 of cover.